A study of prevalence of urogenital problem among menopausal women attending the OPD at tertiary care hospital in Bhopal - Bhardwaj, Malini; Shinde, Tarani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The interest in menopausal problems has increased in recent years, due to the expansion of human life span. Women are spending more than one-third of their lives in menopausal period. Due to this fact, estrogen deprivation can cause vaginal atrophy symptoms and vasomotor symptoms, which critically diminish quality of life (QOL) in postmenopausal women. Methods: This study is a retrospective observational/analytical study conducted in the menopausal specialty clinic in J. K. Hospital, L. N. Medical College, Bhopal over a period of 1 year. All the women who attained menopause either naturally or surgically who presented first time to the clinic for any complaints were evaluated for the UG symptoms with the help of face to face interview. Results: Out of the 300 women with menopausal symptoms, 182 i.e. 60.6% were married and 52% (156) were illiterate. The most prevalent menopausal symptom in present study was vaginal dryness 240 (80%). Conclusions: There is association with lower educational levels. Hence efforts should be made educate women about the symptoms and provide care at all the levels of health care delivery.